Liquid biopsies in gastrointestinal malignancies: when is the big day?. Issue 1 (2nd January 2018) - Lopez, Anthony; Harada, Kazuto; Mizrak Kaya, Dilsa; Dong, Xiaochuan; Song, Shumei; Ajani, Jaffer A.
ABSTRACT: Introduction : Tumor tissue sample is currently the gold standard for diagnosing gastrointestinal cancers, but also for genomic/immune component analyses that can help in the selection of therapy. However, this approach of studying a 'representative' sample of the tumor does not address inherent heterogeneity. Liquid biopsies, mainly represented by circulating tumor cells, circulating tumor DNA, tumor exosomes, and microRNAs, have the potential to assess various biomarkers for early detection of cancer, carrying out genomic/immune profiling for not only selection of appropriate therapy but also to monitor effect of therapy. Areas covered : This review summarizes the current evidence in the literature on liquid biopsies in gastrointestinal cancers concerning diagnosis, prognosis, and response to therapy. The following terms were used in PubMed: 'esophageal', 'gastric', 'colorectal', 'cancer', 'circulating tumor cells', 'circulating tumor DNA', microRNA', 'diagnosis', 'prognosis', 'response', 'resistance'. Expert commentary : Data increasingly supports the potential of liquid biopsies for early detection, selection of therapy, and monitoring response to therapy. One major question is whether assaying various components of the blood would accommodate considerable context-dependent heterogeneity of gastrointestinal tumors. There are many potential strategies to exploit liquid biopsy use. To put them in to perspective, well-designed and meticulous prospective studies will be needed to prove their usefulness.